2007
DOI: 10.1021/jf0700529
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation of Antioxidant Micronutrients in Citrus Juice:  Kinetics and Newly Formed Compounds

Abstract: The thermal degradation kinetics of vitamin C, two carotenoids (beta-carotene and beta-cryptoxanthin), and hesperidin, as a function of temperature, were determined for Citrus juice [Citrus sinensis (L.) Osbeck and Citrus clementina Hort. ex Tan]. The influence of dissolved oxygen on the rate of ascorbic acid degradation was also assessed. Analysis of kinetic data suggested a first-order reaction for the degradation of vitamin C and carotenoids. The kinetics parameters Dtheta, z, and Ea have been calculated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
131
7
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 43 publications
15
131
7
9
Order By: Relevance
“…The activation energy for AA degradation was found as 55.30 kJ/mol. This value is higher than the values of 47.5 kJ/mole for rosehip pulp (Karhan et al 2004) heated under anaerobic circumstances (70-95 ºC), 15.7 kJ/mol for raspberry pulp (Summen & Erge 2014) heated at 60-90 ºC, and lower than the value of 115.5 kJ/mole for orange juice (Johnson et al, 1995) but in good agreement with the activation energies (35.9-94.0 kJ/mol) for ascorbic acid degradation (Dhuique-Mayer et al, 2007;Lima et al, 2010).…”
Section: Thermal Degradation Of Aa Th and Rb In Rhnsupporting
confidence: 68%
“…The activation energy for AA degradation was found as 55.30 kJ/mol. This value is higher than the values of 47.5 kJ/mole for rosehip pulp (Karhan et al 2004) heated under anaerobic circumstances (70-95 ºC), 15.7 kJ/mol for raspberry pulp (Summen & Erge 2014) heated at 60-90 ºC, and lower than the value of 115.5 kJ/mole for orange juice (Johnson et al, 1995) but in good agreement with the activation energies (35.9-94.0 kJ/mol) for ascorbic acid degradation (Dhuique-Mayer et al, 2007;Lima et al, 2010).…”
Section: Thermal Degradation Of Aa Th and Rb In Rhnsupporting
confidence: 68%
“…Ascorbic acid was assessed by HPLC according to Dhuique-Mayer et al (2007). A 10 g sample was weighed and homogenized with 40 mL of metaphosphoric acid solution at 45 g L -1 .…”
Section: Vitamin Cmentioning
confidence: 99%
“…Pharmaceutical supplements and products containing AA are often subjected to thermal treatment during preparation, processing, and storage [25][26][27][28][29]. In case of using AA as a polyurethane chain modifier, it would be also subjected to thermal treatment such as polyurethane synthesis and curing (both carried out at 80°C).…”
Section: Introductionmentioning
confidence: 99%
“…When 5 % v/w moisture was present in a solid ascorbic acid sample, the discoloration was observed, from white to dark brown [31]. Studies on decomposition kinetics of vitamin C in various food products under different storage and processing conditions revealed that decomposition of AA follows with first-order kinetics [25][26][27][28][29]. Jingyan et al also proposed the explanation of three indicated degradation stages of solid ascorbic acid.…”
Section: Introductionmentioning
confidence: 99%